Kesadaran Hak dan Kewajiban Warga Negara Menjaga Lingkungan: Climate Change, Sampah Plastik, dan Green Citizenship - Lenai Situmorang; Bayu Ardian Syahputra; Kezia Thasa Emteta Karina Bangun; Kezia Risky Lumban Gaol; Putri Lopiga Br Tarigan; Vivin Silvia Boang Manalu (CV. Rayyan Dwi Bharata, 2025)
This study examines citizens' awareness of their rights and obligations in protecting the environment, focusing on the issues of climate change, plastic waste, and green citizenship. The results indicate that while Indonesians understand their right to a healthy environment, awareness of their obligations to protect the environment remains low. Active participation in environmentally friendly practices and climate change mitigation is not yet widespread, although the green citizen movement is growing in certain communities. Environmental education and outreach are considered crucial for increasing ecological awareness and public participation. The study recommends regulatory enforcement and education to build a sustainable green citizenship culture to support environmental sustainability and the achievement of the SDGs.